Resposta :
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo-a-passo:
[tex]\mathsf{\dfrac{1 - 2i}{2 + i} = \dfrac{1 - 2i}{2 + i} \times \dfrac{2 - i}{2 -i}}[/tex]
[tex]\mathsf{\dfrac{1 - 2i}{2 + i} \times \dfrac{2 - i}{2 -i} = \dfrac{2 - i - 4i + 2i^2}{4 - 2i + 2i -i^2}}[/tex]
[tex]\mathsf{\dfrac{2 - i - 4i + 2i^2}{4 - 2i + 2i -i^2} = \dfrac{2 - i - 4i - 2}{4 - 2i + 2i + 1}}[/tex]
[tex]\mathsf{\dfrac{1 - 2i}{2 + i} = \dfrac{-5i}{5}}[/tex]
[tex]\boxed{\boxed{\mathsf{\dfrac{1 - 2i}{2 + i} = -i}}} \leftarrow \textsf{letra D}[/tex]